Diversity of fish fauna and water quality at mid-strecth of Batang Rajang at Ng. Benin and Peraran, Kapit, Sarawak - Nadine, Stanley Mopilin (Universiti Malaysia Sarawak (UNIMAS), 2016)
This study was carried out to document the fish composition and to record the status of water quality at midstretch of Batang Rajang. This is due to lack of published report on the fish composition at this area after the construction and operation of Bakun Hydroelectric Dam in 2002 and 2012, respectively. Six stations from downstream area (Ng. Benin) and seven stations from upstream area (Peraran) were selected. The fishes were caught using mono-filament gill nets of different mesh sizes, three layered nets and cast net while YSI Multiparameter was used to measure the water quality parameters in-situ. A total of 477 individuals were caught. Three dominant families are Cyprinidae family (70%), followed by Siluridae (8.6%) and Pangasiidae (6.3%). The three dominant species are Barbonymus schwnenfeldii (10.9%), followed by Cyclocheilichthys apogon (10.48%) and Osteochilus vittatus (5.45%). The Shannon-Weiner diversity index is higher at upstream (Peraran) while Margalef s richness index and Pielou's evnness index is higher at downstream (Ng. Benin). Two out of three species analyzed for length-weight relationship had negative allometric growth. As for water quality, pH ranged from 6.14 to 7.29, turbidity ranged from 6.85 NTU to 299.40 NTU, conductivity ranged from 0.02 μS/cm to 46.60 μS/cm, temperature ranged from 24.48 °C to 28.81 °C, BOD5 ranged from 2.52 mg/L to 5.37 mg/L, chlorophyll-a ranged from 0.0445 gg/L - 1.231 tg/L and TSS ranged from 2.18 mg/L to 83.36 mg/L. The PCA indicates that fishes such as Puntioplites waandersii and Pangasius macronema can tolerate well with stated range of TSS. This study has found that the regulated release of water from Bakun Hydroelectric Dam may have affected the water quality and the diversity of fish in this study area.